ภาวะผู้นำเชิงจริยธรรมของผู้บริหารที่ส่งผลต่อประสิทธิผลของสถานศึกษาในสังคมพหุวัฒนธรรม สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 3 - สาเม๊าะ อับดุลคอเล็บ (Al-HIKMAH Journal, 2021)
The Ethical Leadership of School Administrators Affect to School Effectiveness in Multicultural Society Under the Pattani Primary Educational Service Area Office 3 Abdulkolab Sam0h* , Kanokkorn Sirisuk** *Student Master of Education in Educational Administration, Songkhla Rajabhat University ** Ed.D. (Leadership in Educational Administration), Assistant Professor Educational Administration, Songkhla Rajabhat University Abstract This independent study aimed to 1) study ethical leadership of administrators of schools in multicultural society under the Pattani Primary Educational Service Area Office 3, 2) study effectiveness of schools in multicultural society under the Pattani Primary Educational Service Area Office 3, and 3) study administrators’ ethical leadership that affectced effectiveness of schools in multicultural society under the Pattani Primary Educational Service Area Office 3. The subject were 220 teachers in schools in multicultural society under the Pattani Primary Educational Service Area Office 3 in the A.D. 2021 academic year, using Krejcie and Morgan’s table in setting sample size, the stratified sampling technique in classifying school size and the simple random sampling technique in choosing the subject. Research tools were five-scale questionnaires. Statistics used in this research included percentage, mean, standard deviation and stepwise multiple regression analysis. The findings of the study reveal the following 1) administrators’ ethical leadership of schools in multicultural society under the Pattani Primary Educational Service Area Office 3, both overall picture and each aspect, was at the high level, 2) effectiveness of schools in multicultural society under the Pattani Primary Educational Service Area Office 3, both overall picture and each aspect, was at the high level, and 3) administrators’ ethical leadership that affectced effectiveness of schools in multicultural society under the Pattani Primary Educational Service Area Office 3 consisted of three variables; teamwork development (X5), justice (X3), and sense of service (X2), with the multiple regression analysis value of .633 and prediction discrepancy value of .187 which was able to predict the effectiveness of schools in multicultural society under the Pattani Primary Educational Service Area Office 3 as high as 40.1 percent (R2 = .401). This could create a prediction equation in the form of raw scores and standard scores as follow; = 1.775 + .272 (X5) + .190 (X3) + .127 (X2) = .335 (X5) + .319 (X3) + .173 (X2) Keyword: Administrator’s Ehical Leadership, Effectiveness of School, Multicultural Society